THE STUDY OF PLASMA PARAMETER AND THE EFFECT OF EXPERIMENT SET UP MODIFICATION BY USING MODELLING SOFTWARE - Yunata, Ersyzario Edo; Ghufron, Muhammad (Malaysian Journal of Science, 2019)
Plasma diagnosis has done by using Langmuir probe and software modeling. COMSOL and JMAG software were employed to characterize the electron density and identifying the set up effect in the plasma system. First, the COMSOL software was employed to simulate the behavior of electron density. The pressure and DC-bias voltage were varied during the simulation process. The DC bias voltage was varied in the range -200 V to -600V. The pressure was also varied in the range 30 to 80 Pa. The high electron density was generated in the high DC-bias voltage and high pressure by using simulation process. Second, the Langmuir probe was also employed to measure the behavior of electron density inside the actual plasma chamber. The DC-bias voltage and pressure were also varied in the range - 350V to – 650V and 60 Pa to 120 Pa, respectively. The experiment and modeling result were shown the same trend for the behavior of electron density. Third, the JMAG software was also utilized to characterize and modifying the set up in the plasma system. The electrode and DC bias was varied in the range 100 to 500 V and -100 to -500 V, respectively. The electric field distribution was concentrated in the electrode and DC-bias plate from the original set up. However, the electric field distribution was shifted to the center area after modification process. The modifications of experiment set up have provided the new way to confine the electric field. The high concentrated of electric field was effective to generate high plasma density.